OPTIMALISASI RUTE PENGUMPULAN SAMPAH DI KAWASAN PERUMAHAN PESONA KHAYANGAN DENGAN MODEL PENYELESAIAN TRAVELLING SALESMAN PROBLEM - Sukarmawati, Yuliana; Nahry, Nahry; M. Hartono, Djoko (Jurnal Transportasi, 2013)
The population in Depok is growing in line with the growth of garbage produced. This issue should be balanced with the availability of proper waste management facility, such as providing waste collection vehicles. Pesona Khayangan residence is one of the area in Depok which has waste collection door-to-door service. The limited number of waste collection vehicles make it inefficient to reduce the mounting garbage. This research is aimed to determine the optimal route of waste collection in term of time and cost. The Travelling Salesman Problem is used to model the optimization problem. The solution shows that there is time and distance efficiency on the proposed route and it has successfully saved 50.2 minutes and 0.9 km per service operation.Keywords: waste collection, routing, travelling salesman problem